2006
DOI: 10.1111/j.1528-1167.2006.00845.x
|View full text |Cite
|
Sign up to set email alerts
|

Status Epilepticus after Stroke Is Associated with Increased Long‐term Case Fatality

Abstract: Summary:Purpose: The aim of this study was to determine the long-term case fatality of patients with a first episode of status epilepticus (SE group) of cerebrovascular etiology, as compared with that in acute stroke patients without SE (AS group).Methods: Patients with SE who had been prospectively admitted to an epidemiologic study were retrospectively compared with a cohort of patients from the local stroke registry. The main outcome end point was overall survival. Survival curves were generated according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
2
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 30 publications
2
44
2
4
Order By: Relevance
“…We did not find an increased risk of short-term mortality in patients with PLEDs and/or early epileptic clinical manifestations, which is in contrast to the results reported in other studies [23,25,27,28,29]. The 1-week follow-up design adopted in our study may explain this difference between our results and those of previous studies, which considered mortality rates for up to 30 days after stroke [19,23,24].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…We did not find an increased risk of short-term mortality in patients with PLEDs and/or early epileptic clinical manifestations, which is in contrast to the results reported in other studies [23,25,27,28,29]. The 1-week follow-up design adopted in our study may explain this difference between our results and those of previous studies, which considered mortality rates for up to 30 days after stroke [19,23,24].…”
Section: Discussioncontrasting
confidence: 57%
“…Furthermore, early-onset SE is associated with a higher risk of SE recurrence and a higher mortality [22], although the impact of early seizures on mortality remains a matter of debate. Some studies have indeed found a higher mortality rate in stroke patients with early seizures, at time points ranging from 48 h to 1 year after the event, while other studies that took stroke severity into consideration failed to confirm these findings [19,23,24]. Moreover, in a recent paper, Hesdorffer et al [7] reported that acute symptomatic stroke seizures, when compared with unprovoked seizures, have a higher risk of short-term (30 days) versus long-term (10 years) mortality and a lower risk of subsequent unprovoked seizures, thus arguing against the inclusion of acute symptomatic seizures as epilepsy.…”
Section: Introductionmentioning
confidence: 81%
“…5,6 In particular, experimental studies in multiple mammalian species have demonstrated that SE itself is sufficient to induce cell damage, neurologic comorbidities, and the development of epilepsy, 5 thereby supporting that the occurrence of prolonged unremitting seizures may contribute to pathologic outcomes in humans in addition to underlying pathologies. 7,8 The correlation between SE in preclinical models and humans provides an ideal platform for developing new treatments that can move from laboratory testing to a clinical population with high unmet need. The search for potential therapeutic targets led to the identification of molecular mechanisms underlying SE development in rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Цереброваскуляр-ная патология считается одним из ве-дущих факторов риска эпилепсии у больных старшей возрастной группы [5][6][7][8][9][10][11]. Диагностика эпилепсии у па-циентов позднего возраста представ-ляет определенные трудности, и не-редко заболевание выявляют спустя несколько лет после его начала.…”
unclassified